Annually and monthly resolved solar irradiance and atmospheric temperature data across the Hawaiian archipelago from 1998 to 2015 with interannual summary statistics - Richard Bryce (Data in Brief, 2018)
This article contains data and summary statistics of solar irradiance and dry bulb temperature across the Hawaiian archipelago resolved on a monthly basis and spanning years 1998–2015. This data was derived in association with an article titled “Consequences of Neglecting the Interannual Variability of the Solar Resource: A Case Study of Photovoltaic Power Among the Hawaiian Islands” (Bryce et al., 2018 [7]). The solar irradiance data is presented in terms of Direct Normal Irradiance (DNI), Diffuse Horizontal Irradiance (DHI), and Global Horizontal Irradiance (GHI) and was obtained from the satellite-derived data contained in the National Solar Radiation Database (NSRDB). The temperature data is also obtained from this source. We have processed the NSRDB data and compiled these monthly resolved data sets, along with interannual summary statistics including the interannual coefficient of variability.